PENCEMARAN BAHAN ORGANIK DAN EUTROFIKASI DI PERAIRAN CITUIS, PESISIR TANGERANG - Simbolon, Anna Rejeki (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2016)
Cituis Waters is one that is in the waters of the Coastal Tangerang and directly adjacent to the commercial and port activities in Tangerang and Jakarta. The waters of an estuary of the river that crosses the region Cirarab Tangerang and Jakarta. The high activity of settlements and industries throughout the area of Tangerang and Jakarta generate organik waste and empties into the waters Cituis. High organik matter content in waters will result in eutrophication waters. This study aims to determine the content of organik matter in the waters Cituis and indications of eutrophication in the waters. Sampling of random sampling survey carried out in five sampling points along BOD5ies Cituis April 2013. Descriptive analysis by the Ministry of Environment Decree Number 51 of 2004 on marine water quality standards for water biota. Nitrate and phosphate are high and have passed the quality standards set so that these waters are indicated experiencing eutrofikasi. The content of BOD5 and DO are still in accordance with the quality standards set.